Building a committed workforce: the synergistic effects of coaching leadership, organizational self-esteem, and learning goal orientation - Tang, Leilei; Shi, Mengjuan; Liu, Yu; Liu, Yizhi; Yang, Bingcheng (Frontiers in Psychology, 2024)
In today’s volatile, uncertain, complex, and ambiguous (VUCA) work environments, mitigating employee burnout and turnover has become a critical concern. The enhancement of employee engagement stands out as a pivotal focus in corporate human resource management. Coaching leadership focuses on the encouragement and inspiration of employees, which can effectively stimulate the internal potential of employees, enhance work ability and enhance engagement. However, previous research on the relationship between coaching leadership style and employee engagement are limited, thus obscures the essential function in enterprise development and core competitiveness. The research collected 402 valid responses from MBA and EMBA students at the School of Business, and examines the effect of coaching leadership on employee engagement. Results indicate that coaching leadership significantly enhances multiple facets of employee engagement, including vigor, devotion, and absorption. Crucially, organizational self-esteem emerges as a mediating factor, while learning goal orientation strengthens the positive effects of coaching leadership. This research sheds light on the nuanced dynamics of effective leadership in contemporary workplaces, also it underscores the need for more nuanced, industry-specific analyses and broader exploration of moderating variables. Ultimately, the insights garnered hold profound implications for leadership training, human resource strategies, and performance metrics, emphasizing a more integrative and holistic approach to leadership and employee development in vocational contexts.